White matter alterations in focal to bilateral tonic-clonic seizures - Maher, Christina; D'Souza, Arkiev; Zeng, Rui; Barnett, Michael; Kavehei, Omid; Nikpour, Armin; Wang, Chenyu (Frontiers in Neurology, 2022)
We examined the microstructural white matter in patients with focal epilepsy with focal to bilateral tonic-clonic seizures (FBTCS), focal epilepsy without FBTCS, and control participants. A neural network based tract segmentation model (Tractseg) was used to isolate tract-specific, track-weighted tensor-based measurements from the tracts of interest. We compared the group differences in the track-weighted tensor-based measurements derived from whole and hemispheric tracts. We identified several regions that displayed significantly altered white matter in patients with focal epilepsy compared to controls. Further, patients without FBTCS showed significantly increased white matter disruption in the inferior occipito-frontal fascicle and the striato-occipital tract. In contrast, the track-weighted tensor-based measurements from the FBTCS cohort exhibited a stronger resemblance to the healthy controls (compared to the non-FBTCS group). Our findings revealed marked alterations in a range of subcortical tracts considered critical in the genesis of seizures in focal epilepsy. Our novel application of tract-specific, track-weighted tensor-based measurements to a new clinical dataset contributes to the elucidation of specific tracts that may act as a predictive biomarker to distinguish patients likely to develop FBTCS.